Strengthening prehospital clinical practice guideline implementation in South Africa: a qualitative case study - Michael McCaul; Taryn Young; Stevan R. Bruijns; Mike Clarke (BMC, 2020)
Abstract Background Methods on developing new (de novo) clinical practice guidelines (CPGs) have received substantial attention. However, research into alternative methods of CPG development using existing CPG documents (CPG adaptation) - a specific issue for guideline development groups in low- and middle-income countries - is sparse. There are only a few examples showcasing the pragmatic application of such alternative approaches in settings with time and budget constraints, especially in the prehospital setting. This paper aims to describe and strengthen the methods of developing prehospital CPGs using alternative guideline development methods through a case study design. Methods We qualitatively explored a CPG development project conducted in 2016 for prehospital providers in South Africa as a case study. Key stakeholders, involved in various processes of the guideline project, were purposefully sampled. Data were collected from one focus group and six in-depth interviews and analysed using thematic analysis. Overarching themes and sub-themes were inductively developed and categorised as challenges and recommendations and further transformed into action points. Results Key challenges revolved around guideline implementation as opposed to development. These included the unavoidable effect of interest and beliefs on implementing recommendations, the local evidence void, a shifting implementation context, and opposing end-user needs. Guideline development and implementation strengthening priority actions included: i) developing a national end-user document; ii) aligning recommendations with local practice; iii) communicating a clear and consistent message; iv) addressing controversial recommendations; v) managing the impact of interests, beliefs and intellectual conflicts; and vi) transparently reporting implementation decisions. Conclusion The cornerstone of a successful guideline development process is the translation and implementation of CPG recommendations into clinical practice. We highlight key priority actions for prehospital guideline development teams with limited resources to strengthen guideline development, dissemination, and implementation by drawing from lessons learnt from a prehospital guideline project conducted in South Africa.